Analysis Of The Company's Reputation and Logistics Innovation Against The Competitive Advantage That Mediated Service Satisfaction at PT BGR Indonesia - Sehat Nirwansyah Sinurat; Elfitra Desy Surya; Erwansyah (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of company reputation and logistics innovation on competitive advantage mediated by service satisfaction at PT BGR Indonesia. The increasingly fierce competition in the logistics industry requires companies to strengthen their image and customer trust and innovate in distribution systems, technology, and service processes. This study uses a quantitative approach with a survey method through the distribution of questionnaires to customers. The data was analyzed using Structural Equation Modeling (SEM) to test the relationships between variables. The results of the study show that company reputation and logistics innovation have a positive and significant effect on service satisfaction. Furthermore, service satisfaction has a significant effect on competitive advantage. The mediation test proves that service satisfaction partially mediates the influence of the company's reputation and logistics innovation on competitive advantage. These findings underscore the importance of reputation-based and innovation-based strategies to sustainably improve the company's competitiveness.